Social TV: definição sobre a experiência do usuário - Américo, Marcos [UNESP]; Santos, Paulo Araújo dos (Instituto Educacional Piracicabano da Igreja Metodista, 2013)
This article presents a study on the concept of social TV and the user’s experience. We made a literature review in search of the several meanings and features given to the subject. We have analyzed the aspects that express changes in the field, beginning with the TV set connected to the internet, which allows users to new experiences of socialization, previously available only in other devices. This new scenario provides a new platform called “TV everywhere”, the ubiquitous television that is everywhere, regardless of location, time or space. We have researched the origin of social TV and the process that altered the old television model. Finally, we propose a new term to express such changes regarding social television: “Social TV”, representing the user’s experience through the convergence between television and the Internet, shared locally and remotely through any technological means.

Este artigo apresenta um estudo sobre o conceito de televisão social a partir da experiência do usuário. Busca, na literatura, os diversos sentidos e características que são dados ao tema. São analisados aspectos que expressam as mudanças no meio, partindo da televisão conectada à internet, que permite ao usuário novas experiências de socialização, antes disponíveis apenas em outros dispositivos. Esse novo cenário possibilita uma nova plataforma chamada de TV everywhere , a televisão onipresente, aquela que está em toda parte, independente de local, tempo ou espaço. Procura-se a origem da televisão social e como se deu o processo que alterou a televisão de fluxo. Por fim, propõe um novo verbete que expresse essas mudanças relacionadas à televisão social. Define-se assim, Sócio-TV como a experiência obtida pelo usuário pela convergência entre televisão e internet, que pode ser compartilhada local ou remotamente através de qualquer meio tecnológico.
Social TV: a definition about the user’s experience
Keywords: Digital TV; Social TV; TV everywhere; Smart TV; Social-TV